The Deterioration Effects of Consumer Indebtedness on Consumer and Brand Relationships: When Gift Giving is not Appreciated - Suetrong, Prapatsorn (Asia Social Issues, 2023)
Most literature on gift giving has focused on positive feelings between giver and receiver in contexts of family members or close friends. This concept is applied to gift giving strategies that used to establish positive consumer and brand relationships. However, these strategies may not result in pleasurable outcomes in all cases because they entail consumer psychological damage such as dissatisfaction and indebtedness. With a different perspective, this study investigates how negative gift giving experiences impact consumer and brand relationships. Online questionnaires were used to collect data in Thailand. Structural equation modelling results showed that negative gift giving experiences cause consumer dissatisfaction and consumer indebtedness. These feelings lead to brand hate and brand avoidance. The results also revealed the mediating role of consumer indebtedness. The results contribute theoretical insight into brand relationships and lead to recommendations on marketing practice.